Determination of caffeine in different brands of coffee samples by Solid Phase Microextraction (SPME) and Gas Chromatography Mass Spectrometry Detector (GC-MSD) / Nur Elywati Khalib - Khalib, Nur Elywati (2010)
Caffeine in different brands of coffee samples (Li, L2, Ii, and I2) was determined using extraction by solid phase microextraction (SPME) and then analyzed by gas chromatography coupled with mass spectrometry detector (GC-MSD). The optimizations of SPME were carried out in order to enhance the fiber performance and obtain high amount of caffeine extracted. The optimization conditions were done by extracting 500 ppm of caffeine standard solution. It was found that the optimum SPME conditions were at 85 °C of extraction temperature and 10 minutes of extraction time. The headspace immersion of SPME was applied to extract caffeine from different brands of coffee samples. The result showed that I2 brand of coffee has the relatively highest amount of caffeine among the four brands analyzed. This was followed by Ii, Li and L2 brands of coffee.